Oxidative stress, inflammation, and apoptosis in Alzheimer’s disease associated with HSV-1 and CMV coinfection - Sepideh Khodamoradi; Forouzan Khodaei; Taher Mohammadian; Atousa Ferdousi; Fatemeh Rafiee (Virology Journal)
Abstract Oxidative stress, inflammation, and apoptosis have been reported to influence cognitive function in patients with Alzheimer’s disease (AD), particularly those infected with herpes simplex virus type 1 (HSV-1) or cytomegalovirus (CMV). This study aimed to evaluate the effects of viral infection on oxidative stress markers associated with these pathways in AD patients. A total of 100 adults with mild-to-moderate AD were randomly assigned to a double-blind, placebo-controlled clinical trial and categorized into three groups: AD (uninfected), AD with HSV-1, and AD with CMV. The primary outcomes included changes in serum inflammatory markers (IL-1β and TNF-α), blood antioxidant and oxidative stress markers—glutathione peroxidase (GPx), superoxide dismutase (SOD), malondialdehyde (MDA), reactive oxygen species (ROS), and total antioxidant capacity (TAC), as well as the expression levels of apoptosis-related proteins (BAX and BCL-2). Results showed that, compared to the control group, the AD group exhibited significant alterations in inflammatory and oxidative stress markers. CMV infection led to increased antioxidant enzyme activity and decreased serum inflammatory markers relative to the uninfected AD group. However, there were significant differences in ratio BAX/BCL-2 protein expression between the CMV and HSV-1 groups when compared to the AD group. In conclusion, AD patients infected with HSV-1 or CMV demonstrated distinct alterations in inflammatory, oxidative stress, antioxidant profiles, and apoptosis markers, which may have beneficial implications for circulatory biomarkers and potentially cognitive outcomes in AD.